2006
DOI: 10.1109/tuffc.2006.186
|View full text |Cite
|
Sign up to set email alerts
|

Microwave leakage-induced frequency shifts in the primary frequency Standards NIST-F1 and IEN-CSF1

Abstract: In atomic fountain primary frequency standards, the atoms ideally are subjected to microwave fields resonant with the ground-state, hyperfine splitting only during the two pulses of Ramsey's separated oscillatory field measurement scheme. As a practical matter, however, stray microwave fields can be present that shift the frequency of the central Ramsey fringe and, therefore, adversely affect the accuracy of the standard. We investigate these uncontrolled stray fields here and show that the frequency errors ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…Heavner et al considered that the amplitude dependence of "any microwave lensing shift scales just like the microwave leakage shift," which is proportional to δν/ν= A n sin(n π/2) = A' φ sin(φ) (dashed curve in Fig. 1a and, in [1], Fig 6), reporting measurements with Rabi pulse areas of φ=n π/2 for n=1,3,5, … [1,7,14,16]. Previously, we have shown that the microwave lensing shift scales as δν/ν ∝ φ 1 /sin(φ 1 ) [2][3][4], where φ 1 (2) is the Rabi pulse area in the first (second) Ramsey interaction.…”
mentioning
confidence: 99%
“…Heavner et al considered that the amplitude dependence of "any microwave lensing shift scales just like the microwave leakage shift," which is proportional to δν/ν= A n sin(n π/2) = A' φ sin(φ) (dashed curve in Fig. 1a and, in [1], Fig 6), reporting measurements with Rabi pulse areas of φ=n π/2 for n=1,3,5, … [1,7,14,16]. Previously, we have shown that the microwave lensing shift scales as δν/ν ∝ φ 1 /sin(φ 1 ) [2][3][4], where φ 1 (2) is the Rabi pulse area in the first (second) Ramsey interaction.…”
mentioning
confidence: 99%
“…Similarly the frequency shift at n=5 is 5 times that at n=1, and the shift at n=7 is -7 times that at n=1 etc. Thus, for data taken at odd integer multiples of the pattern of frequency shifts is identical to that from microwave leakage below the Ramsey cavity [6].…”
Section: Model and Resultsmentioning
confidence: 78%
“…The microwave synthesizer which generates the microwaves for state-selection is attenuated and strongly detuned when the atoms are outside the state-selection area and therefore cannot induce a frequency bias. Microwave-leakage induced frequency-biases resulting from leakage above the Ramsey interaction cavity is precluded in our fountains by the design of the drift region and has a different behaviour vs. microwave amplitude in any case [5][6][7][8]. This leaves microwave leakage after the second Ramsey interaction as the only possible source of leakage induced frequency bias.…”
Section: Model and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the full uncertainty evaluation can be made, the uncertainty in the microwave power dependence shift will be evaluated by measuring the frequency as a function of the microwave power [40] or using an interference switch to suppress the influence of the microwave leakage on the atoms in the interrogation region [41]. Next, other type B uncertainties will be reduced by further experiments, such as the measurement of the long-term variation in the magnetic field in the interrogation region, and by monitoring the temperature of the vacuum chamber.…”
Section: Discussionmentioning
confidence: 99%